Integrated Farming Model Strategy For Developing The Islamic Boarding School Economy - Fathor Rakhman; Miftahus Surur; Feb Amni Hayati; Zaki Emyus; Akhmad Ramli (Mudir : Jurnal Manajemen Pendidikan, 2023)
Islamic boarding schools as religious institutions have great potential in efforts to develop the economy and welfare of Islamic boarding schools, as well as a strong influence on the life of the Islamic boarding school community. Therefore, the Islamic boarding school established an integrated farming business unit as a means to develop the economy and welfare of the school. This study aims to describe and analyze: the process of Islamic boarding school economic development through integrated farming units; the results of Islamic boarding school economic development through integrated farming units; as well as supporting and inhibiting factors for the economic development of Islamic boarding schools through integrated farming units. To answer the formulation of the problem, researchers used a qualitative approach. The results of this study indicate that the economic development carried out by Islamic boarding schools through integrated farming units has succeeded in increasing their economic income and creating jobs, as well as increasing the knowledge, skills, and experiences of students and their surroundings society about aquaculture and modern agriculture.